Importance of information technology (IT) knowledge in brokering of oil and gas in international business - Singh, Satnam (Universiti Malaysia Sarawak (UNIMAS), 2014)
Study Objective: 6 he objective of this study is to look at the key competencies of a successful broker mainly the IT knowledge and its importance in the brokering competence of Oil and Gas business. The study is to analysis if there is a relationship between Information Technology (IT) Knowledge and Broker Information Technology (IT) competence in Oil and Gas business transactio, Design/methodology/approach: This research used a descriptive approach which employed the quantitative research method in collecting and analyzing data via questionnaire to study the relationship between IT knowledge and brokers' competence. Findings: The study is conducted using SPSS version 20.0 by using frequency analysis, One Sample t-test and Pearson Correlation test to determine relationship between the importance of IT knowledge and the various IT specific areas which demonstrate broker competencies. Results: The results demonstrate a significant relationship between IT knowledge and broker competencies; however as IT knowledge is important the data shows the brokers may not be competent enough to use it for successful Oil and Gas ~usiness transactions and may require fUl1her training for greater development.